PENERAPAN PENDEKATAN SAINTIFIK DENGAN METODE DISKUSI KELOMPOK UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS MATERI MENGHARGAI PERJUANGAN PARA TOKOH DALAM MEMPERTAHANKAN KEMERDEKAAN - Wahyuni, Sri Endah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The purpose of this research is to increase student motivation and learning outcomes/result of 5th-grade SDN 1 Karanganyar Patikraja Banyumas for Social lesson with the topic to Appreciating the Characters Struggle to maintain independence through the application of the scientific approach. This Research is using Classroom Actions Research which implemented in two cycles, each cycle consisting of four stages, those stages are planning/designs, actions, observations, and reflections. Data collection can be done by test, observation, and questionnaire. An indicator of the success of actions in this research is if the increase of student motivation is at least 80% from the maximal score from all students and if the increased of learning outcomes is at least 85% from all students has to reach KKM of Social lesson 68. This research concludes that: First, Application of the Scientific Approach with group discussion method can increase student motivation in the social lesson for the topic to Appreciating the Characters Struggle to maintain the independence of 5th-grade SDN 1 Karanganyar Patikraja Banyumas.